Identification and validation of reference genes for quantitative gene expression analysis under 409 and 415 nm antimicrobial blue light treatment - Kruszewska-Naczk, Beata; Grinholc, Mariusz; Rapacka-Zdonczyk, Aleksandra (Frontiers in Molecular Biosciences, 2025)
IntroductionReverse transcription quantitative real-time polymerase chain reaction Q7 (RT‒qPCR) is a commonly used tool for gene expression quantification. Because the qPCR method depends on several variables that can influence the analysis process, stably expressed genes should be selected for relative gene expression studies. To date, there is insufficient information on the selection of appropriate reference genes for antimicrobial photodynamic inactivation (aPDI) and antimicrobial blue light (aBL) treatment. Therefore, the purpose of the present study was to determine the most stable reference gene under treatment with aBL under sublethal conditions and to evaluate differences in the expression of the selected gene after aBL treatment in comparison to the nontreated control.MethodsSelection of stable reference genes was performed using 4 programs: BestKeeper, geNorm, NormFinder and RefFinder under 409 and 415 nm aBL treatment.ResultsThe results revealed that the gene encoding the integration host factor β subunit (ihfB) in Escherichia coli was the most stably expressed gene after both 409 and 415 nm aBL treatment. Three programs, RefFinder, geNorm, and NormFinder, indicated that this gene had the most stable expression in comparison to the other reference gene candidates. The next best candidates were cysG, uidA, and gyrA. NormFinder revealed ihfB as the single gene and cysG - gyrA as the combination of reference genes with the best stability.DiscussionUniversal reference genes are characterized by stable expression that remains consistent across various stress conditions. Consequently, it is essential to evaluate reference genes for each specific stress factor under investigation. In the case of aBL at different wavelengths, we identified genes that maintain stable expression following irradiation.